2014
DOI: 10.1371/journal.pone.0087113
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Analyses of a Well-Differentiated Liposarcoma Reveals Novel SYT1 and DDR2 Rearrangements

Abstract: Liposarcoma is the most common soft tissue sarcoma, but little is known about the genomic basis of this disease. Given the low cell content of this tumor type, we utilized flow cytometry to isolate the diploid normal and aneuploid tumor populations from a well-differentiated liposarcoma prior to array comparative genomic hybridization and whole genome sequencing. This work revealed massive highly focal amplifications throughout the aneuploid tumor genome including MDM2, a gene that has previously been found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Surgical excision is the primary treatment modality used for DDLPS, as DDLPS exhibits a low response rate to conventional chemotherapeutic reagents 4 . To date, several analyses have unveiled genomic characteristics common to DDLPS, including the amplification of 12q13-15, that are also frequently found in WDLPS 510 . These studies have also identified a number of genes within 12q13-15, including HOXC13, MDM2 , HMGA2 , CDK4 , and CPM , as being key to the development of DDLPS and WDLPS; a number of additional genomic occurrences, such as the loss of 11q23 and the gain of 6q23 and 1p32, have been defined as genomic abnormalities that are specific to DDLPS 6,8,1117 .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical excision is the primary treatment modality used for DDLPS, as DDLPS exhibits a low response rate to conventional chemotherapeutic reagents 4 . To date, several analyses have unveiled genomic characteristics common to DDLPS, including the amplification of 12q13-15, that are also frequently found in WDLPS 510 . These studies have also identified a number of genes within 12q13-15, including HOXC13, MDM2 , HMGA2 , CDK4 , and CPM , as being key to the development of DDLPS and WDLPS; a number of additional genomic occurrences, such as the loss of 11q23 and the gain of 6q23 and 1p32, have been defined as genomic abnormalities that are specific to DDLPS 6,8,1117 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar oncogene activation by L1-ASP has been reported in other cancer types, such as MET activation in bladder cancer [35, 78, 79]. SYT1 is a protein-coding gene found to facilitate the export of the oncogenic growth factor FGF-1 [71]. The promoter activity of L1PA2- SYT1 in breast cancer cell lines coincided with its increased DNAse sensitivity and decreased DNA methylation, suggesting the L1PA2- SYT1 element can promote expression of the proto-oncogene SYT1 .…”
Section: Discussionmentioning
confidence: 70%
“…It is also thought to function in the adult nervous system and the gene has been associated with schizophrenia. Whole genome analysis revealed a gene fusion between UHMK1 and DDR2 In well-differentiated liposarcoma [32]. IL6RInterleukin 6 receptormRNA: Yes 30 TPMProtein: N/AThe receptor of IL6 which is involved in the regulation of the immune response.…”
Section: Resultsmentioning
confidence: 99%